MACHINE OVER MIND? THE CLASH OF AGENCY IN SOCIAL MEDIA ENVIRONMENTS - McConnell, Stephen Joseph (AoIR Selected Papers of Internet Research, 2023)
Underlying many social media platforms are personalization engines designed to give people instant content and social recommendations to keep them engaged, yet understanding of their cognitive and behavioral impacts remains limited, particularly how user agency may be altered during interactions with these tools.In interviews and focus groups, a diverse sample of 45 participants offered their experiences with these tools where they reflected on how they responded and reacted to them, and how they felt they preserved their agency or had it eroded by the technology. Participants also reported several novel outcomes that occurred that they attributed to the tools, including falling down "rabbit holes" where time and conscious thinking appeared to dissolve -- outcomes they did not anticipate happening.Drawing from social cognitive theory, this dissertation advances an explanatory model that demonstrates the interactional dynamic between individuals and these choice recommendation engines, as well as identifies core agency, and related cognitive and behavioral, processes that appear to be activated during the interaction.As a practical contribution, this work demonstrates individuals can have the upper hand in these environments, so long as they have a clear understanding of the consequences of use of these tools. The model provides that guidance, building on past social cognitive work that sought to empower individuals to be free, non-constricted agents who can attain any realistic goal they desire, so long as they exercise their internal capacities to achieve it and have an awareness of the environments that may thwart it.